Building Maintenance & Construction Tools and Maintenance Tasks - Rutherford, Clifford; Open Textbook Library (Open Textbook Library, 2018)
Building Maintenance & Construction: Tools and Maintenance Tasks introduces and develops knowledge of basic building maintenance tools and materials, applied skills and techniques, industry health and safety standards, and preventive maintenance and troubleshooting practices required by employers for entry-level positions in the building trades and facilities maintenance fields.
Part 1: Safety -- 1.1 First Aid & Personal Protective Equipment -- 1.2 Eye and Face Protection -- 1.3 Hearing Protection -- 1.4 Head Protection -- 1.5 Hand Protection -- 1.6 Respiratory Protection -- 1.7 Foot Protection -- 1.8 Tool & Shop Safety -- 1.9 Ladder Safety & Fall Protection -- Part 2: Hand & Power Tools -- 2.1 Tool Choices and Applications -- 2.2 Measuring, Marking, Leveling & Layout Tools -- 2.3 Nails, Hammers & Pneumatic Nailers -- 2.4 Threaded Fasteners, Drivers, Pliers & Wrenches -- 2.5 Saws -- 2.6 Drills & Accessories -- 2.7 Grinders, Sanders, & Accessories -- Part 3: Mathematics for Maintenance Techs -- 3.1 Required Math Concepts -- 3.2 Ohm's Law, Joules Law, and Series/Parallel Formulas -- Part 4: Plumbing Systems -- 4.1 Piping & Fittings -- 4.2 Domestic Water Service -- 4.3 Drain, Waste, and Vent (DMV) -- 4.4 Valves & Prevention Devices -- 4.5 Faucets, Fixtures, & Fixture Drains -- 4.6 Plumbing for Appliances -- 4.7 Water Heating -- Part 5: Electrical Systems -- 5.1 Electrical Safety -- 5.2 Electrical Tools & Testing Equipment -- 5.3 Electrical Terminology & Lighting -- 5.4 Conduit, Boxes, & Wiring -- 5.5 Fuses & Breakers -- 5.6 Receptacle & Switch Wiring -- 5.7 Outdoor Wiring Considerations -- Part 6: Maintenance Management Systems -- 6.1 Maintenance Categories -- 6.2 Work Order Process -- 6.3 Parts and Material Resources
In English.
Description based on print resource
Keywords: Engineering -- Textbooks; Civil -- Textbooks